Rehabilitation of patients with benign vocal fold lesions - O. V. Kotyanina (Бюллетень сибирской медицины, 2009)
Benign vocal fold lesions is the largest group of larynx diseases. At the present time the fundamental principle in treatment of benign laryngeal lesions is the combined therapy including surgical, medical and phonopedic methods of voice rehabilitation by indications.